The culture of civil war in Kyoto - Berry, Mary Elizabeth, 1947- (A Philip E. Lilienthal book, 1994)
After 1467, war became commonplace in Japan. This book explores that commonplace--the everyday terrain of violence that men and women traced in their diaries, their suits and petitions, their marches and rebellions, their dancing. This is not a book about battles, causes, and resolutions. It is a book about the backwash of battle in a great city, the murkiness and volatility of purpose that marked ever new conflicts. It is about the absence of closure--the resistance to closure--in a long war that broke apart medieval attachments and identities to require fearsome trials with alternatives.